Public health approach to preventing frailty in the community and its effect on healthy aging in Japan. (March 2016) - Shinkai, Shoji; Yoshida, Hiroto; Taniguchi, Yu; Murayama, Hiroshi; Nishi, Mariko; Amano, Hidenori; Nofuji, Yu; Seino, Satoshi; Fujiwara, Yoshinori
Abstract : Effective methods to prevent or delay the onset of frailty are urgently required in aging societies, such as Japan. As a public health approach, we carried out a 10‐year community intervention for frailty prevention, and examined its impact on healthy aging among older adults. The target population was all residents aged 65 years or older in the town of Kusatsu, Gunma Prefecture, Japan. For community empowerment, we organized a community forum, and discussed how to address the frailty issue in the community. For primary prevention, we attempted to promote physical activity, nutrition and social participation by means of a health education program to motivate older residents. For secondary prevention, we added a comprehensive geriatric assessment to routine annual health check‐ups, which helped older participants improve self‐care ability of functional health. High‐risk persons were screened and encouraged to participate in a frailty prevention class with a multicomponent program. The attendance rate at annual health check‐ups has remained constant at 30–40% of the target population; however, over 80% of the population appeared at least once during the 10 year‐period. For evaluation, we carried out biennial health monitoring surveys, and reviewed the records of the local Long‐Term Care Insurance system. The functional health of older residents was significantly improved as a result of the interventions; the incidence rate of Long‐Term Care Insurance system certification in the old‐old population (age ≥75 years) was decreased by one second, and healthy life expectancy at age 70 years was extended by 1.2 years for women and 0.5 years for men. Such trends greatly contrasted with those in the reference area, and Japan as a whole. In summary, the present public health approach to frailty prevention appears to promote healthy aging among older adults.Geriatr Gerontol Int 2016; 16 (Suppl. 1): 87–97.